INTERNAL CONTROL, ORGANIZATIONAL CULTURE, AND FRAUD PREVENTION IN FINANCIAL MANAGEMENT AT THE KIBIN COMMUNITY HEALTH CENTER UPT - Nur Ferah; Didin Rasyidin Wahyu; Ombi Romli (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
Fraud prevention is an essential element in establishing accountable and transparent public financial governance. This study examined the relationship between internal control and organizational culture and fraud prevention in financial management at UPT Puskesmas Kibin, Serang Regency. A quantitative approach with an associative design was employed. The study involved all 40 employees responsible for financial management using a saturated sampling technique. Data were collected through a Likert-scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, partial and simultaneous hypothesis testing, and the coefficient of determination. The findings indicate that organizational culture has a positive and significant relationship with fraud prevention, whereas internal control does not demonstrate a significant partial relationship. Simultaneously, both variables explain 39.6% of the variation in fraud prevention. These findings emphasize the importance of strengthening organizational culture to improve integrity in public financial management.